Effect of rib arrangements on the flow pattern and heat transfer in internally ribbed rectangular divergent channels. (2021) - Sivakumar, K.; Sampath Kumar, T.; Sivasankar, S.; Ranjithkumar, V.; Ponshanmugakumar, A.
Abstract: In this article, a numerical investigation is conducted to analyze three-dimensional incompressible Navier-strokes flows through the rectangular divergent square ribbed channels with different Reynolds number value 20, 000, 40, 000 and 60, 000 having five different configurations of square ribs (p/e = 2.5, 3.33, 5, 10, and 20) has been used as roughness element. The commercial finite-volume based CFD code ANSYS FLUENT is used to simulate turbulent airflow through the channels. The RNG k-ε turbulence model is used to solve the transport equations for turbulent flow energy and dissipation rate. Detailed results about average heat transfer and fluid friction in a rectangular divergent square channel are presented and discussed.